Discovering traces of the past : studies of bilingualism among school pupils in Finland and in Sweden - Kuure, Olli (Acta Universitatis Ouluensis. Series E. Scientiae rerum socialium, 1997)
Tiivistelmä: Menneisyyden jäljillä : tutkimuksia peruskoululaisten kaksikielisyydestä Suomessa ja Ruotsissa.